The age associations of blood pressure, cholesterol and glucose: analysis of health examination surveys from international populations - Singh, Gitanjali M (2012)
BACKGROUND: The age-association of cardiovascular disease (CVD) may be partially because its metabolic risk factors tend to rise with age. Few studies have analyzed age-associations of multiple metabolic risks in the same population, especially in nationally representative samples. We examined worldwide variations in the age associations of systolic blood pressure (SBP), total cholesterol (TC), and fasting plasma glucose (FPG). METHODS AND RESULTS: We used individual records from 83 nationally or sub-nationally representative health examination surveys in 52 countries to fit a linear model to risk factor data between ages 30-64 years for SBP and FPG, and between 30-54 years for TC. We report the cross-country variation of the slope and intercept of this relationship. We also assessed non-linear associations in older ages. Between 30 and 64 years of age, SBP increased by 1.7-11.6 mmHg per ten years of age and FPG increased by 0.8-20.4 mg/dL per ten years of age in different countries and in the two sexes. Between 30 and 54 years of age, TC increased by 0.2-22.4 mg/dL per ten years of age in different surveys and in the two sexes. For all risk factors and in most countries, risk factor levels rose more steeply among women than among men, especially for TC. On average, there was a flattening of age-SBP relationship in older ages; TC and FPG age associations reversed in older ages, leading to lower levels in older ages than in middle ages. CONCLUSIONS: The rise with age of major metabolic CVD risk factors varies substantially across populations, especially for FPG and TC. TC rises more steeply in high-income countries and FPG in the Oceania countries, the Middle East, and the US. The SBP age association had no specific income or geographical pattern.